2021
DOI: 10.1111/jdv.17581
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of vesiculobullous non‐IgE‐mediated cutaneous reactions to tozinameran (Pfizer‐BioNTech COVID‐19 vaccine)

Abstract: had a slightly higher incidence of facial skin problems than those with oily skin. Changes in the facial microbiome might partly explain the skin problems caused by long-term mask wearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…From the systematic review, we identified 300 articles 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ...…”
Section: Resultsunclassified
See 2 more Smart Citations
“…From the systematic review, we identified 300 articles 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ...…”
Section: Resultsunclassified
“…From the systematic review, this report has described various cutaneous manifestations associated with the COVID‐19 vaccine including injection site reactions, 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 which were the most common cutaneous adverse reaction in almost all vaccines, uncommon adverse reactions such as delayed inflammatory reactions to tissue filler, 73 , 127 , 228 , 279 flares of pre‐existing dermatoses (e.g. psoriasis, 103 , 133 , 137 , 141 , 215 , 239 , 248 , 252 , 282 , 312 bullous pemphigoid, 63 , 111 pemphigus vulgaris, 111 , 121 lichen planus, 85 , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for exclusion included no discussion of vesicular, papulovesicular, or bullous reactions ( n = 167). Twenty-seven 12 , 13 , 17 - 41 of the 36 articles described nonspecific vesicular, papulovesicular, or bullous reactions, compared to eleven 18 , 24 , 42 - 50 discussing vesicular eruptions in concordance with new-onset or reactivation of the herpes zoster virus. During the screening process, a total of 66 articles discussing other cutaneous manifestations were retrieved from the full-text screening to extract data in tabular formats and were discussed in our narrative review.…”
Section: Resultsmentioning
confidence: 99%
“…This delayed cutaneous manifestation may be related to the host immune cytokine response rather than true allergies, an observation similar to Juay et al in their 3 cases of vesiculobullous cutaneous reactions to tozinameran. 4 Other vaccines, such the MMR vaccine, have also been previously demonstrated to exacerbate atopic dermatitis via elevated IL-4 levels, disrupting the Th1 and Th2 lymphocytic balance. 5 COVID-19 vaccinations have been reported in association with many cutaneous side effects in many local institution-based studies.…”
Section: Dear Editormentioning
confidence: 99%